Evaluating critical thinking elements in a secondary school English language textbook in Malaysia - Ng, Qing Yi; Joseph Jeyaraj, Joanna (Human Resources Management Academic Research Society (HRMARS), 2023)
Despite increasing calls to develop critical thinking (CT), Malaysian students struggle with CT due to the lack of opportunities to engage with these thinking skills in the classroom. In this study, we explore the potential for CT engagement within the context of English language education by focussing on a prescribed textbook that is used in secondary schools nationwide. We sought to determine CT elements infused into English Download B1+ Student's Book and to explore how the textbook encouraged the use of CT among students. Quantitative content analysis was utilised to analyse and evaluate CT elements in the textbook and qualitative content analysis was employed to further examine and explicate textbook tasks. Instruments used included the Cambridge Assessment Taxonomy of Critical Thinking, California Critical Thinking Disposition Inventory (CCTDI), and CT activities from Jebbour’s (2019) analysis checklist. Our analysis revealed that CT activities had the highest frequency of occurrence, followed by CT skills, and lastly CT dispositions. Therefore, we recommend more opportunities for CT dispositions to be developed through textbook tasks. Additionally, while the presence of CT activities in textbook was observed, we suggest a greater variety of tasks to address the teaching of the four main language skills.